Evaluation process use in the University Capacity Development Programme at Walter Sisulu University - Mantshongo, Mandla (My University, 2021)
The study investigated the effect of evaluation process use as a mechanism in the performance of the University Capacity Development Grant at Walter Sisulu University (WSU). The significance of the study was to enlighten the project leaders who participated in the evaluation process to acknowledge the changes that have arose, and the learning associated with that the process. Literature identified the lack of clearly defined measures of the process changes with regards to the performance of projects in the context of higher education and further understanding of the effectiveness of the involvement or engagement of stakeholders in the process of evaluation. This research adopted the qualitative approach as the method that was utilised in collecting the data. Both primary and secondary data collection methods were used to undertake this study in the form of semi-structured interviews through Microsoft Teams adopted due to the COVID-19 restrictions, focus groups, and document review in the form of progress reports and assessment reports. Fifteen participants participated in the data collection with seven individual semistructured interviews and two focus groups each made up of four participants. The findings of the study demonstrated that: (1) individual thinking or behavioural change cannot be solely attributable to process use as there are other factors that contribute to change, (2) the change and performance could be measured or viewed differently at different levels such as at individual, institutional, evaluators and funders/DHET level, (3) Learning is inevitable to the stakeholders involved in the process, however, the skill transfer to other members who did not participate in the process is lacking, (4) non-conceptualised and non-researched interventions and (6) no convergence in findings for implementation that influences the change of institutional culture. Overall, at individual and project level there are glaring changes in implementation of a project rather than on the performance of UCDG.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Monitoring and Evaluation 50% to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2020
Keywords: Evaluation; University Capacity Development Programme; Evaluation process; SDG-8: Decent work and economic growth; SDG-4: Quality education